Identification of Regulatory-RNAs for Alternative Splicing of Ron Proto-Oncogene - Moon, Heegyum (J Cancer, 2015)
RON receptor tyrosine kinase is a proto-oncogene that induces cell migration and matrix invasion. RONΔ160 protein, which is produced by exclusion of exon 5 and 6, promotes cell migration, matrix invasion and protection from apoptosis. Alternative splicing regulation of exon 5 and 6 is not well understood. In this manuscript, we identified several new RNA regulatory elements for alternative splicing of Ron proto-oncogene. Firstly, we demonstrated that RNA sequences from EcoRI cleavage sites regulate alternative splicing of Ron exon 5 and 6. Secondly, we showed that the ~30 nt RNA at upstream end of exon 4 and the ~33 nt RNA at downstream end of exon 7 also modulate splicing of exon 5 and 6. Thirdly, our results indicate that the RNA sequences of the ends in exon 4 and 7 are required for the regulatory functions of the RNA from restriction enzyme cleavage sites. Our results provide a new insight for regulation of alternative splicing of Ron proto-oncogene.